Freedom of Expression, Commercial Expression and Tobacco in Canada - Reid, Caroline (Victoria University of Wellington Law Review, 2008)
The application of freedom of expression protections to commercial expression is a matter of some debate. Some commentators suggest that commerciality robs expression of the value inherent in more politically, culturally, or socially motivated expression. In Canada, the Supreme Court has found that commercial expression is entitled to protection. The affirmation of these rights subject “only to such reasonable limits prescribed by law as can be demonstrably justified in a free and democratic society” does, however, allow for the commercial nature of expression to be weighed as against the value of allowing such expression. The Supreme Court’s approach to freedom of commercial expression, as exemplified by the tobacco cases, indicates that this right is not given the same degree of protection as non-commercial expression. However, the Court’s approach and refusal to introduce a specific test allows flexibility in application, and provides for the possibility that, in some cases, protections may be broad enough to place commercial expression on a par with non-commercial expression.